The Effect of Cooperative Learning Models and Learning Motivation towards the Skills of Reading Students in Public Elementary School 101883 Tanjung Morawa Sub-district - Utari Nur Wulandari; Khairil Ansari; Wisman Hadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to: (1) Know the differences in reading skills of students taught with Cooperative Integrated Reading and Composition learning models compared to students taught with conventional learning models; (2) Knowing the difference in reading skills of students who have high learning motivation compared to students who have low learning motivation; (3) Knowing the interaction between learning models and learning motivation in influencing students' reading skills. The population in this study was the fifth grade students of Public Elementary School 101883 Tanjung Morawa Subdistrict, Deliserdang Regency, amounting to 54 people. The data collection in this study was through a questionnaire and a test of students' reading skills. Hypothesis testing is done by the Two Way Anova test. The results showed that: (1) The reading skills of students taught with Cooperative Integrated Reading and Composition learning models were higher than those of students who were taught with conventional learning models (Fcount = 21,164 and sig. 0,000> 0.05); (2) The reading skills of students who have high learning motivation are higher than the reading skills of students who have low learning motivation (Fcount = 6.756 and sig. 0.012> 0.05); (3) There is an interaction between learning models and learning motivation in influencing students' reading skills (Fcount = 7.054 and sig. 0.011> 0.05).